2016
DOI: 10.1111/ejn.13177
|View full text |Cite
|
Sign up to set email alerts
|

An obesity‐associated risk allele within the FTO gene affects human brain activity for areas important for emotion, impulse control and reward in response to food images

Abstract: Understanding how genetics influences obesity, brain activity and eating behaviour will add important insight for developing strategies for weight-loss treatment, as obesity may stem from different causes and as individual feeding behaviour may depend on genetic differences. To this end, we examined how an obesity risk allele for the FTO gene affects brain activity in response to food images of different caloric content via functional magnetic resonance imaging (fMRI). Thirty participants homozygous for the rs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
44
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 42 publications
5
44
1
1
Order By: Relevance
“…3A) did not replicate previously reported effects in adults. Moreover, none of these prior studies in adults reported effects in the ventral striatum of the kind that we observed in children, either because these effects were not present (14,16) or the effects were not examined (15). As such, it is difficult to reconcile the current findings in children with those previously reported in adults.…”
Section: Discussioncontrasting
confidence: 81%
See 4 more Smart Citations
“…3A) did not replicate previously reported effects in adults. Moreover, none of these prior studies in adults reported effects in the ventral striatum of the kind that we observed in children, either because these effects were not present (14,16) or the effects were not examined (15). As such, it is difficult to reconcile the current findings in children with those previously reported in adults.…”
Section: Discussioncontrasting
confidence: 81%
“…It is worth noting, however, that even within the cohorts of adults tested previously, there is little consistency in reported effects across studies. Moreover, with one exception (14), none of the prior work links FTO genotypic differences to neural differences in canonical reward regions despite the fact that previous studies have demonstrated a causal role of FTO in regulating dopaminergic transmission (12) and also in modulating mesocorticolimbic circuitry in adults (13). The effects reported here in children in ventral striatum function and structure, as well as the voxel-wise whole-brain exploratory analysis, constrain the FTO genotypic differences to canonical reward neurocircuitry.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations